Η Βυζαντινή οικογένεια των Αγιοθεοδωριτών ΙΙ: Μιχαήλ Αγιοθεοδωρίτης, πρωτονωβελισσιμοϋπέρτατος λογοθέτης του δρόμου και ορφανοτρόφος - ΜΑΔΑΡΙΑΓΑ Ελισάβετ (Byzantina Symmeikta, 2015)
Michael Hagiotheodorites was the brother of Nicholas Hagiotheodorites, Metropolitan of Athens (ca. 1166-1175) and, as we believe, also of the mesazon (1143 - ca. 1155) John (1) Hagiotheodorites. He was certainly one of the most illustrious and powerful officials of Manuel I Comnenus. By 1158/59, he was already the man of confidence (in his capacity of mesazon and after succeeding Theodore Styppeiotes also as epi tou kanikleiou) of Manuel I Comnenus. Logothete tou dromou from 1166, Eustathius tells us that he died shortly before the death of the emperor himself, namely Michael died ca. 1179-1180. Since the year 1166, he holds in addition the office of Orphanotrophe of Constantinople. If not earlier, at least after 1175, he became a member of the clergy of St. Sophia and also took up monastic life (but he held political office until his death!). The latter finding strengthens our belief that Michael died being childless.